2021
DOI: 10.1111/tbj.14303
|View full text |Cite
|
Sign up to set email alerts
|

Lower lymph node yield in axillary lymph node dissection specimens in breast cancer patients receiving neoadjuvant chemotherapy: Quality concern or treatment effect?

Abstract: Axillary lymph node dissection (ALND) specimens should have at least ten‐lymph nodes for examination according to established guidelines. Nonetheless, recent evidence suggests that neoadjuvant chemotherapy (NAC) results in fewer nodes in the specimen. We sought to examine if NAC patients have lower lymph node yield from ALND specimens and whether the number of lymph nodes in the specimen is correlated with pathologic complete response (pCR). Using the National Cancer Database (NCDB), a study cohort of female p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In a retrospective study using data from the National Cancer Database, it was found that the yield of axillary lymph node dissection was significantly lower in patients received neoadjuvant chemotherapy than those who underwent surgery alone, and that patients received neoadjuvant chemotherapy were more likely to not meet the criteria of axillary lymph node dissection. In addition, the study also found that low lymph node yield was independently associated with pCR of the primary tumor ( 36 ). With the development of chemotherapy regimens and targeted anti-HER2 treatment, the primary tumor and axillary pCR rates have increased substantially.…”
Section: Discussionmentioning
confidence: 94%
“…In a retrospective study using data from the National Cancer Database, it was found that the yield of axillary lymph node dissection was significantly lower in patients received neoadjuvant chemotherapy than those who underwent surgery alone, and that patients received neoadjuvant chemotherapy were more likely to not meet the criteria of axillary lymph node dissection. In addition, the study also found that low lymph node yield was independently associated with pCR of the primary tumor ( 36 ). With the development of chemotherapy regimens and targeted anti-HER2 treatment, the primary tumor and axillary pCR rates have increased substantially.…”
Section: Discussionmentioning
confidence: 94%